Large-Scale 3D Chips: Challenges and Solutions for Design Automation, Testing, and Trustworthy Integration - Knechtel, Johann; Sze, Cliff C. N.; Elfadel, Ibrahim (Abe) M.; Lienig, Jens; Sinanoglu, Ozgur (IPSJ Transactions on System LSI Design Methodology, 2017)
Three-dimensional (3D) integration of electronic chips has been advocated by both industry and academia for many years. It is acknowledged as one of the most promising approaches to meet ever-increasing demands on performance, functionality, and power consumption. Furthermore, 3D integration has been shown to be most effective and efficient once large-scale integration is targeted for. However, a multitude of challenges has thus far obstructed the mainstream transition from “classical 2D chips” to such large-scale 3D chips. In this paper, we survey all popular 3D integration options available and advocate that using an interposer as system-level integration backbone would be the most practical for large-scale industrial applications and design reuse. We review major design (automation) challenges and related promising solutions for interposer-based 3D chips in particular, among the other 3D options. Thereby we outline (i) the need for a unified workflow, especially once full-custom design is considered, (ii) the current design-automation solutions and future prospects for both classical (digital) and advanced (heterogeneous) interposer stacks, (iii) the state-of-art and open challenges for testing of 3D chips, and (iv) the challenges of securing hardware in general and the prospects for large-scale and trustworthy 3D chips in particular.